Creation of a Regional Edition of Ruwiki (a Case of the Komi-Language Edition) - Marina Fedina (Современные информационные технологии и IT-образование)
The article is devoted to an analytical description of the creation of a regional edition of the new online encyclopedia Ruwiki. The combination of the latest digital and language technologies with 20 languages of the peoples of Russia determines the entire complex of features that influence the creation of not only the overall system of Ruwiki but also its regional-language editions. Using the example of the Komi language, emerging problems, intralinguistic and extralinguistic features are analyzed. Intralinguistic features include purely linguistic capabilities of the edition, such as existence of necessary terminology, possibilities for neology, etc. Extralinguistic features refer to digital infrastructure (keyboard layouts, electronic dictionaries, digital resources, including digital encyclopedias, libraries, etc.), human resources (availability of specialists proficient in computer technologies and specific language; volunteers), availability and accessibility of source materials for writing encyclopedia articles, technical support, financial costs, time factor, etc. An important feature of the regional edition is its personification. One or two people are responsible for each edition, unlike, for example, the Russian edition with an entire team working on it. Each editor of a regional edition is multifunctional: they localize, search for and verify materials, ensuring their accuracy, write articles in the native language on various topics, train volunteers, review the edits and articles made by them, and learn new technologies daily.